PERANCANGAN ALAT ALARM PENDETEKSI BANJIR MENGGUNAKAN NODEMCU BERBASIS INTERNET OF THINGS (IOT) - Pajar Septian; Nurjaya (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Internet of Things (IoT) is one of the technologies that are currently developing. IoT allows it to be used to control and monitor the use of electricity consumption in a place remotely via a smartphone. One of the IoT supporting devices for monitoring electrical energy consumption is a Smart Socket. Because of its usefulness, the author tries to make a control system and monitor electricity consumption based on ESP12E using IoT. The method used to create an ESP-12E-based control and monitoring system for electrical energy consumption using IoT is an experimental method. The ESP-12E-based electrical energy consumption control and monitoring system using IoT consists of a smart socket prototype and an Android application. For communication needs, HTTP protocol and IoT Platform are used. The results showed that smart phones can be used to control the Smart Socket prototype and retrieve information about the total energy consumption of each socket. While the Smart Socket can calculate the total consumption of electrical energy and send it to the IoT Platform. Smart Socket has been successfully created and can function properly. Flood is a natural disaster event that occurs when excessive water flows submerge land. The European Union's flood directive defines a flood as a temporary submergence by water of land that is not normally submerged in water. This study aims to create a flood detection control application based on the Bylnk App using Android. This system can help the user to know the distance of the water level from a certain distance and to activate the alarm. Nodemcu is the main controller on the detection alarm device. This study uses android as a notification display. The Nodemcu receives commands sent from the Ultra Sonic Sensor device and is forwarded to the Nodemcu. And Nodemcu will turn on the Buzzer which is an alarm that informs the current water level and activates an alarm if flood water comes.